Extending Kohut's Concept of Selfobject: The Undifferentiated Selfobject. - Rowe, Crayton (Clinical Social Work Journal, 2013)
This paper highlights and adds to the understanding of the undifferentiated selfobject, an extension of Kohut's contributions of mirror, twinship and idealizing selfobjects. Introduced by Rowe in (), the undifferentiated selfobject follows Kohut's teaching that there are still selfobjects that have not been discovered and which, therefore, have remained unanalyzed. This paper offers an understanding of the importance of the undifferentiated selfobject in the treatment of a depressed and potentially suicidal woman.